Design of the fully differential operational floating conveyor and its applications - ElGemmazy, Hossam (AUC Knowledge Fountain, 2018)
Analog circuits can be generally classified into two broad categories: The first one includes analog circuits operating in the voltage mode, while the second category includes those operating in the current mode. Voltage mode analog circuit’s bandwidth is highly dependent on the gain via the gain bandwidth product (GBP). To solve this problem, many current mode circuits are developed such as the second generation Current Conveyor (CCII) and the Operational Floating Conveyor (OFC). A novel concept of the Fully Differential Operational Floating Conveyor (FD-OFC) is presented for the first time, to the best of the author’s knowledge. A CMOS design for the proposed FD-OFC is introduced as an 8 (4x4) port general purpose analog building block. The FD-OFC design is implemented using two different realizations. The proposed design has the advantage of low power consumption as it operates under biasing conditions of only 1.2 V while its wide bandwidth reaches 600 MHz. These operating conditions recommend the proposed device to be integrated to a wide range of low power-wide high speed applications. The terminal behavior of the proposed device is mathematically modeled and its operation is simulated using the UMC 130 nm technology kit in Cadence environment. Differential voltage amplifier, current mode instrumentation amplifier (CMIA) and Fully Differential second generation Current Conveyor (FDCCII) are examples of the presented applications based on the proposed FD-OFC.